An Antimicrobial Metabolite from Bacillus sp.: Significant Activity Against Pathogenic Bacteria Including Multidrug-Resistant Clinical Strains - Chalasani, Ajay G.; Dhanarajan, Gunaseelan; Nema, Sushma; Sen, Ramkrishna; Roy, Utpal (Frontiers in Microbiology, 2015)
In this study, the cell free modified trypticase soya broth (pH 7.4+0.2) of Bacillus subtilis URID 12.1 showed significant antimicrobial activity against multidrug-resistant strains of Staphylococcus aureus, S. epidermidis, Streptococcus pyogenes and Enterococcus faecalis. The partially purified antimicrobial molecule was found to be resistant to extremes of pH and temperatures and also to higher concentrations of trypsin and proteinase K. The antimicrobial molecule was purified by a three-step method that included reverse-phased high performance liquid chromatography (RP-HPLC). The minimum inhibitory concentration (MIC) values were determined for 11 species of bacteria using a microbroth dilution technique. The HPLC-purified fraction showed the MICs ranging from 0.5 to 1 µg/ml for methicillin and vancomycin resistant Staphylococcus aureus (MVRSA) and methicillin-resistant Staphylococcus epidermidis (MRSE) strains. The molecular mass of the antimicrobial compound was determined to be 842.37 Da. The same antimicrobial fraction showed negligible haemolytic activity against human red blood cells even at a concentration as high as 100µg/ml. Because of its significant antimicrobial activity at low MIC values coupled with its non-haemolytic property, it may prove to be a novel antimicrobial lead molecule.